HUBUNGAN PENGETAHUAN DENGAN KEPATUHAN DIET PADA PENDERITA DIABETES MELLITUS DI POSYANDU LANSIA CEMPAKA KELURAHAN TEMBOK DUKUH KECAMATAN BUBUTAN SURABAYA - Nobel Bistara, Difran; Ainiyah, Nur (Jurnal Ilmiah Kesehatan, 2018)
Diabetes mellitus (DM) is a degenerative disease that can be controlled with the four pillars of management. One of the pillars is compliance in the implementation of the diet "3J". This study aims to determine the relationship of knowledge with dietary compliance in patients with DM in Posyandu Lansia Cempaka, Tembok Dukuh, Bubutan, Surabaya. The study design is analytic correlation with approach cross sectional. Sample research is patients with DM in Posyandu Lansia Cempaka the active come Posyandu Lansia of as many as 33 patients. The independent variable is the knowledge of diet DM. The dependent variable is a dietary compliance in patients with DM. Analysis of data using correlation coefficient with somers test. The results showed that people with diabetes who have a good knowledge of most of the diet compliance in the diet is also good. The results of the analysis test Somers obtained pvalue of 0.000 means that there is a relationship between knowledge and dietary compliance in patients with DM, with level of closeness 0,154 (0,00 <| r | ? 0,20) with significance of closeness that is very low or very weak. Recommendations on these results in order to develop methods of collecting data through interviews and observations to gain a more realistic picture of the data. Also developed variables that affect the knowledge and compliance such as the characteristics of respondents and family support.